“Smart” cities: The new paradigm of urban development - Kesić, Dušan (Sociološki pregled, 2023)
The progress achieved in the field of ICT has caused a major change in the paradigm of urban development, and research directed towards the development of smart cities is characterized as a central interest of modern society. Smart cities are designed as a kind of panacea for the accumulated problems of urban development. Although this idea is rooted in the achievements of ICT, the contemporary understanding of the concept implies that the smart city goes beyond the mere application of technology. Moreover, the holistic perspective emphasizes the primacy of human and social capital as the supporting pillars of a smart city. Considering the above, the aim of this paper is to achieve a systematic insight into the evolution of the smart city concept, that is, to see the peculiarities of its conceptualization, key dimensions and indicators, as well as the relationship to similar concepts.